Legal Issues in Health Care (Out of Print) - Carol Schwab (Association of American Medical Colleges, 2009)
Abstract Legal Issues in Health Care is an online interactive program that includes tutorials, factsheets, and StudyMate activities designed to teach legal and ethical issues involved in the practice of medicine. The materials provide a wide choice of activities to address different learning styles. The online tutorials are in PowerPoint format, and they provide a quick, bare-bones overview of specific topics for the busy student, resident, fellow, or practitioner. They were developed as a result of numerous requests for a quick overview of the basic legal and ethical principles that pervade the practice of medicine. A set of factsheets were developed to supplement a one-hour lecture series. The factsheets provide a general overview of the topics and may be printed to give the learner a tangible product to review at his or her leisure. These factsheets were well received by fourth-year medical students. The included StudyMate activities provide numerous learning activities, such as a quiz, crossword puzzles, a challenge game, flash cards, etc., that are designed to promote learning while having fun. They were used as a "textbook" for a week-long intersession with second year medical students. The multiple-choice questions embedded in the program contain explanations of why the correct answer is the most appropriate choice, providing a more in-depth study for the more serious learner. Tennessee law is featured in this program, but the principles discussed are relevant in all jurisdictions. The materials serve as a firm foundation for teaching the legal issues in health care. However, students have consistently stated that the materials are most appropriately used as a supplement to lectures and class discussions.